New Zealand and Slovenia : cultural contacts, 1923-2000 - Andrej Podbrežnik (Acta Neophilologica)
Situated many thousands of miles apart, possessing very different historical experiences and occupying different positions in the world, Slovenia and New Zealand nonetheless share a number of common features as a result of the political, economic and cultural contacts that have been estab lished between the two countries. The author of this paper attempts to gauge the intensity of the contacts, mostly cultural, that have been forged between the two countries, with an emphasis on descriptions of New Zealand and portrayals of its people in the work of some of Slovenia's most outstanding travel writers. Alma Karlin (Samotno potovanje), Miran Ogrin (Na jugu sveta) and Tomo Križnar (Samotne sledi) have all succeeded in acquainting the Slovene reading public with New Zealand and its people and culture. So that readers might understand more fully the observa tions offered by these writers, the author of this paper provides background information in the{orm of a short account of the history of New Zealand and of New Zealand literature, going on to focus on those New Zealand writers whose work has been translated into Slovene, most notably Katherine Mansfield. Other writers whose work has been translated include Janet Frame, Dorothy Eden, Ngaio Marsh, Stephanie Johnson and Samuel Butler.